Improved method for isotopic measurement of free‐living nitrogen fixation - Zhou, Qianchen; Mulvaney, Richard L.; Nunes, Vander L. N. (Soil Science Society of America journal, 2025)
The use of 15N‐labeled dinitrogen (15N2) affords the only direct means of measuring free‐living nitrogen fixation (FLNF); however, progress in utilizing this approach has been impeded by methodological limitations arising from the presence of nitrogenous contaminants, a lack of atmospheric uniformity, and incomplete description of procedural details. Such constraints are eliminated with an ex situ technique comprehensively described herein, which involves circulating 15N2 generated by hypobromite oxidation through a closed system that includes chemical (sulfuric acid–potassium permanganate) and cryogenic (isopentane–liquid N2) traps for atmospheric purification and an incubation chamber consisting of a desiccator equipped with a pressure gauge. Studies to evaluate the circulation system described showed that a uniform atmosphere was readily achieved with a 10‐L desiccator by pumping for 30 min, and that both chemical and cryogenic traps were necessary to ensure complete (98.8%–99.6%) removal of gaseous contaminants subject to physicochemical retention by sterilized soil samples. The method proposed was successfully demonstrated in detecting the stimulatory effect of organic carbon (C) on FLNF in active soils, and can be further utilized to improve the reliability of ex situ assessment of FLNF in relation to soil processing and storage, climatic conditions, microbial dynamics, and land management practices. Core Ideas Direct measurement of free‐living nitrogen fixation (FLNF) is constrained by existing 15N methods. An ex situ method is described in detail for incubating samples in a desiccator containing purified 15N2. A demonstration was conducted using this method to verify treatment effects on FLNF. The method proposed eliminates constraints regarding atmospheric contamination and variability.